Implementasi Metode Pembelajaran Berbasis Game Bisik Berantai Dalam Meningkatkan Daya Ingat Siswa Di MTs Al-Amin Jenu - Alfiatin, Alfiatin; Rohmatin, Rohmatin (Jurnal Pendidikan Agama Islam Miazhar, 2026)
This study aims to examine the effectiveness of the chain whisper game-based learning method in improving the memory performance of seventh-grade students at Mts Al-Amin Jenu. This research employed a Pre-Experimental approach using the One Group Pre-test Post-test design with a single experimental group. Data were collected through pretest–posttest assessments and analyzed using the Paired-Samples T-Test. The results indicate a significant improvement in students’ memory scores, as reflected by the value of t = -12.717 (df = 11) with p = 0.000 (p < 0.05). These findings demonstrate that the chain whisper activity effectively enhances students’ focus and working memory processes by requiring active listening, information processing, and accurate reproduction. The positive impact is reinforced by a more interactive and engaging learning atmosphere that reduces monotony commonly found in conventional teaching methods. Therefore, the chain whisper game-based learning method serves as an innovative pedagogical strategy to strengthen students’ cognitive abilities, particularly memory retention, while improving overall classroom learning dynamics.